The Influence of Age and Sexual Drive on the Predictive Validity of the Juvenile Sex Offender Assessment Protocol-Revised - Wijetunga, Charity (International journal of offender therapy and comparative criminology, 2018)
The Juvenile Sex Offender Assessment Protocol-Revised (J-SOAP-II) is the most commonly used measure in the assessment of recidivism risk among juveniles who have committed sexual offenses (JSOs), but mixed support exists for its predictive validity. This study compared the predictive validity of the J-SOAP-II across two offender characteristics, age and sexual drive, in a sample of 156 JSOs who had been discharged from a correctional facility or a residential treatment program. The J-SOAP-II appeared to be a better predictor of sexual recidivism for younger JSOs (14-16 years old) than for older ones (17-19 years old), with significant differences found for the Dynamic Scale and Scale III (Intervention). In addition, several of the measure’s scales significantly predicted sexual recidivism for JSOs with a clear pattern of sexualized behavior but not for those without such a pattern, indicating that the J-SOAP-II may have greater clinical utility for JSOs with heightened sexual drive. The implications of these findings are discussed.